Pembelajaran PAI Berbasisi Empat Pilar dalam Meningkatkan Hasil Belajar Siswa - Muthia Zahra; Khairatul Uswah; Gusmaneli Gusmaneli (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to explore the influence of Islamic Religious Education (PAI) learning based on the four pillars of education Learning to Know, Learning to Do, Learning to Be, and Learning to Live Together on improving student learning outcomes. its effect on improving student learning outcomes. The results show that the implementation of the four pillars of education significantly improves students' understanding of PAI materials, as well as develops their social and emotional skills. The end result of the implementation of the four pillars of education is that students can not only obtain good learning outcomes in the intellectual aspect, but can also improve in their spiritual aspect.